Pembuatan Horizontal Spindle Test bar pada Mesin Frais Aciera F3 - Risky Ayu Febriani; Novi Saksono; Herman Budi Harja; Rian Wijaya (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2024)
A test bar is a tool that represents an axis whose position will be tested relative to other machine elements as well as the movement of the axis relative to its own position. With a test bar as a precision tool, the deviation value of a machine's geometry can be determined. In the initial stages of making the spindle test bar, namely determining the design according to ISO 230-1:1996 standards, machine testing tools books and directly observing the Aciera F3 Milling Machine. The stages of making a test bar spindle consist of several machining processes such as the lathe process, heat treatment and grinding process, quality checking, and testing. The results of the quality check showed that there were 4 actual dimensions within the tolerance limits and 3 other actual dimensions had sizes outside the tolerance limits, but sizes outside these limits had no effect on the function of the workpiece being made, so this calibration tool could still be used. For testing the spindle test bar on the Aciera F3 Milling Machine object, there were deviations in eccentricity and parallelism with the transverse direction table of 0.030 mm and 0.011 mm, respectively.